2022
DOI: 10.1039/d2nj00176d
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Au/ZnO catalyzed aerobic benzyl alcohol oxidation by modulation–excitation attenuated total reflection IR spectroscopy

Abstract: The chemisorbed or dissociated oxygen species is associated with the catalytic activity in alcohol oxidation catalyzed by Au/ZnO catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…−1 h −1 was obtained over Au/TiO 2 −C 3 N 4 catalysts in the absence of light irradiation, and TiO 2 −C 3 N 4 was inert under identical reaction conditions. These results suggested that benzyl alcohol can also be activated and converted over Au particles by hot electrons even at ambient temperature, 44,45 and hot electrons contribute approximately 20% to benzyl alcohol conversion. Finally, the Au/TiO 2 −C 3 N 4 ternary composites exhibited good durability in the photocatalytic oxidation of benzyl alcohol as the conversion rates were not significantly changed after the fifth run as delineated in Figure 5c.…”
Section: Investigation Of the Ba Photooxidationmentioning
confidence: 91%
“…−1 h −1 was obtained over Au/TiO 2 −C 3 N 4 catalysts in the absence of light irradiation, and TiO 2 −C 3 N 4 was inert under identical reaction conditions. These results suggested that benzyl alcohol can also be activated and converted over Au particles by hot electrons even at ambient temperature, 44,45 and hot electrons contribute approximately 20% to benzyl alcohol conversion. Finally, the Au/TiO 2 −C 3 N 4 ternary composites exhibited good durability in the photocatalytic oxidation of benzyl alcohol as the conversion rates were not significantly changed after the fifth run as delineated in Figure 5c.…”
Section: Investigation Of the Ba Photooxidationmentioning
confidence: 91%
“…A reactive distillation column was used to assess the catalytic effectiveness. While the Zr 1−x Al x O y catalysts offered outstanding TTF efficiency for the synthesis of propylene carbonate (PC) and MeOH, the typical amphoteric compounds, including ZrO 2 , Al 2 O 3 and ZrO 2 + Al 2 O 3 , provided low conversion and selectivity for the formation of DMC [ 5 , 36 ]. The Zr 0.5 Al 0.5 O y catalyst had the highest PC conversion of 98.1% at 99.9% DMC selectivity among the catalysts.…”
Section: Developed Methods For Green Dmc Synthesismentioning
confidence: 99%
“…However, the detailed mechanism is still unable to reveal this. (5) Via the characterization of ATR-IR spectra to dig out the possible reaction intermediates [63], we have clearly mapped out the whole conversion pathway and worked out the controversy in this photocatalysis.…”
Section: Conclusion Challenges and Future Perspectivementioning
confidence: 99%